2022
DOI: 10.1001/jamaoncol.2022.0615
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Toxic Effects and Survival in Treatment Deescalation With Radiotherapy vs Transoral Surgery for HPV-Associated Oropharyngeal Squamous Cell Carcinoma

Abstract: IMPORTANCEThe optimal approach for treatment deescalation in human papillomavirus (HPV)-related oropharyngeal squamous cell carcinomas (OPSCCs) is unknown.OBJECTIVE To assess a primary radiotherapy (RT) approach vs a primary transoral surgical (TOS) approach in treatment deescalation for HPV-related OPSCC. DESIGN, SETTING, AND PARTICIPANTSThis international, multicenter, open-label parallel-group phase 2 randomized clinical trial was conducted at 9 tertiary academic cancer centers in Canada and Australia and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 14 publications
1
58
0
Order By: Relevance
“…Multiple studies report favorable swallowing outcomes using TORS for resection of oropharyngeal cancers (12-18). Additionally, the phase 2 randomized ORATOR and ORATOR2 trials demonstrated similar MDADI scores for the RT and TORS treatment arms of their studies up to 3 years of follow up (19,20). Taken together, patient reported quality-of-life is at least comparable, if not better, for TORS when compared to CRT.…”
Section: Functional and Oncologic Outcomes Of Transoral Surgery Versu...mentioning
confidence: 89%
“…Multiple studies report favorable swallowing outcomes using TORS for resection of oropharyngeal cancers (12-18). Additionally, the phase 2 randomized ORATOR and ORATOR2 trials demonstrated similar MDADI scores for the RT and TORS treatment arms of their studies up to 3 years of follow up (19,20). Taken together, patient reported quality-of-life is at least comparable, if not better, for TORS when compared to CRT.…”
Section: Functional and Oncologic Outcomes Of Transoral Surgery Versu...mentioning
confidence: 89%
“…In an attempt to preserve organ function, avoid surgical complications and potentially achieve excellent treatment outcomes with decreased toxicity, some studies have focused on reduction of the primary RT dose. A randomized phase II study (ORATOR2) compared upfront TORS plus ND followed by a reduced-dose adjuvant RT (50 Gy in 25 fractions or 60 Gy in 30 fractions if there were positive margins or ENE) with a primary de-escalated RT (60 Gy) with weekly cisplatin 40 mg/m 2 [ 72 ]. Overall, 61 patients with T1-2 N0-2 AJCC 8th edition HPV+ OPSCC were randomized; 31 in the TORS group and 30 in the primary RT group.…”
Section: Treatment Deintensificationmentioning
confidence: 99%
“…Patients in both treatment arms in ORATOR2 achieved good swallowing outcomes at one year after the treatment. Grade 2–5 adverse events occurred in 67% of the patients in the RT group compared to 71% in the TORS group [ 72 ]. Careful patient selection and high-level surgical expertise in high-volume centers are of paramount importance for an uncomplicated procedure of TORS in HPV+ OPSCC.…”
Section: Treatment Deintensificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The ORATOR-2 trial is a prospective phase II randomized trial comparing definitive deintensified CRT and transoral surgery [ 32 ]. Patients were eligible as T1-2N0-2M0 according to the AJCC, 8th edition, which also represents T1-2N0-2 by the AJCC, 7th edition.…”
Section: Deintensification Of Definitive Crtmentioning
confidence: 99%